5-HT3 blockade does not attenuate postspinal blood pressure change in cesarean section: A case-control study. Issue 36 (4th September 2020) - Neumann, Claudia; Velten, Markus; Heik-Guth, Cornelia; Strizek, Brigitte; Wittmann, Maria; Hilbert, Tobias; Klaschik, Sven
Abstract : Abstract: Spinal anesthesia (SpA) for elective caesarean section (CS) is often accompanied by clinically relevant arterial hypotension. The Bezold-Jarisch reflex, causing postspinal hypotension, has been shown to be antagonized by serotonin type 3 (5-HT3 ) blockade. Our aim was to assess if routine prophylactic administration of the 5-HT3 antagonist ondansetron (ODS) attenuates postspinal change in maternal blood pressure. Elective CS under SpA were retrospectively analyzed. Eighty parturients having routinely received 8 mg ODS prior to SpA were compared with 80 patients having not (control group). Mean arterial blood pressure significantly decreased from baseline to the postspinal period ( P  < .0001) without differences in blood pressure decreases between the 2 groups. This also applied to the heart rate. Overall use of cafedrine/theodrenaline was higher in the ODS group (0.8 (0.4–1.6) mL vs 0.8 (0–1.0) mL in the control group, P  = .01). APGAR values showed a presumably clinically irrelevant decrease in control group compared with the ODS group. Our results suggest that routine administration of ODS in a dosage of 8 mg does not effectively attenuate postspinal change in maternal blood pressure during CS in our setting. Given the wide variability of anesthetic techniques, only large prospective and randomized multicenter trials will ultimately serve to elucidate this issue.